The Essence of Terrorism: We Are Different - Minderop, Albertine (UI Scholars Hub, 2019)
This research entitled: The Essence of Terrorism: We Are Different was written with the aim of showing that a strong belief in an ideology or a religion can lead to the concepts of the self (we) and the other (they). Thought about this concept gave an issue to a sense of difference and animosity towards other parties. This party must be destroyed because